2001
DOI: 10.1002/jbm.1068
|View full text |Cite
|
Sign up to set email alerts
|

The wear pattern in metal‐on‐metal hip prostheses

Abstract: The accumulated data suggest that there is a strong correlation between polyethylene wear and osteolysis, which ultimately leads to prosthetic loosening. Second-generation metal-on-metal prostheses have been introduced, with an eye toward resolving this wear-induced osteolysis problem. The metal particles and ions are biologically active and can affect the cell homeostasis. Thus, defining the wear pattern and ratio of a given metal-on-metal prosthesis system is desirable. An early high-wear or run-in phase fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…MOM bearings have been reintroduced in orthopaedics because they exhibit reduced wear and osteolysis compared with standard metal-on-polyethylene bearings [2,9,21,33]. This is important in young, active patients because the increased level of function exposes the implant to greater cumulative mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOM bearings have been reintroduced in orthopaedics because they exhibit reduced wear and osteolysis compared with standard metal-on-polyethylene bearings [2,9,21,33]. This is important in young, active patients because the increased level of function exposes the implant to greater cumulative mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although MOM-THA is in widespread use [24], concerns remain regarding wear and corrosion of the bearing surfaces and the subsequent increase in serum metal ion levels [2,8,10,18,28]. All metal implants corrode at a rate which is determined partly by their surface area [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, questions have arisen as to the correspondence between the wear particles generated in vitro and those observed clinically in vivo (Savio et al, 1994). Nevertheless, hip simulator studies have proven particularly useful in identifying the wear pattern/profile of total hip systems; thus such studies have shown that unlike MOP systems which show linear ratios of wear over time, modern MOM prostheses have an early high wear ratio phase (run-in) followed by a lower wear ratio phase (steady-state) (Anissian et al, 2001). The same biphasic profile is observed also with modern COC articulations (Hatton et al, 2002) and it is speculated that the initial wear phase is due to a polishing effect resulting from the motion of the head against the cup (Mode 1 wear) while the following phase is mostly due to third body wear.…”
Section: Wear Rates and The Choice Of Modern Bearings For Young Patientsmentioning
confidence: 99%
“…In 2006, MOM bearing surfaces were utilized in 35 % of the total hip arthroplasties (THAs) performed in the USA [2]. Advantages of MOM bearing surfaces include significantly lower volumetric wear rates, decreased rates of instability due to the ability to use a large femoral head, and high fracture toughness compared to ceramic-on-ceramic bearing surfaces [1,3,4]. However, there have been prominent clinical concerns over unique failure modes over the past decade [1,5].…”
Section: Introductionmentioning
confidence: 99%